Design and experimental results of passive iUSBL for small AUV navigation. (15th March 2022) - Wang, Yingqiang; Huang, S.H.; Wang, Zhikun; Hu, Ruoyu; Feng, Mingyue; Du, Peizhou; Yang, Wencheng; Chen, Ying
Abstract: This paper presents a passive inverted Ultra-Short Baseline (piUSBL) positioning system which provides accurate and instantaneous positioning for small Autonomous Underwater Vehicles (AUVs) at low cost and power consumption. Conventional underwater positioning systems tend to be expensive and bulky, limiting the application of small AUVs. This system is based on an iUSBL positioning system, which places a small circular receiver array on an AUV rather than on a deployment ship. The One-Way Travel-Time (OWTT) range and Direction of Arrival (DOA) between the vehicle and a single acoustic beacon enable AUV navigation relative to the beacon. Deconvolved conventional beamforming (dCv) provides high-resolution azimuth estimation. This paper describes the system design in detail and presents experimental results in an anechoic tank and some field lakes. The piUSBL system shows great potential for small AUVs after several successful AUV applications. Highlights: piUSBL provides accurate and instantaneous positioning for AUV navigation. One-way travel-time ranging reduces system complexity and weight. Deconvolved CBF (dCv) of a small circular array is proved to be feasible. piUSBL shows great potential in multi-AUV applications.